2004
DOI: 10.1007/s00330-004-2354-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of styloid process by three-dimensional computed tomography

Abstract: The purpose of this paper was to investigate the length, medial angulations and other structural variants of the styloid process (SP) by three-dimensional computed tomography (3D CT) in patients without any complaints related to elongated SP. We performed temporal computed tomography (CT) scans in 138 cases (87 males, 51 females) with a mean age of 34.5 (17-86). The structure, length and medial angulation of SPs were evaluated on 3D reconstructed images. SP lengths varied between 1.58 and 5.48 cm (average leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
73
4
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 13 publications
16
73
4
9
Order By: Relevance
“…In a study by Ramadan et al it was seen that the MLA was 67-76 [17] and in a study by Basekin et al [23] it was 65-75 [23] which is in close proximity to the present study. Length and MLA also showed no correlation with the length of SHC.…”
Section: Discussionsupporting
confidence: 88%
“…In a study by Ramadan et al it was seen that the MLA was 67-76 [17] and in a study by Basekin et al [23] it was 65-75 [23] which is in close proximity to the present study. Length and MLA also showed no correlation with the length of SHC.…”
Section: Discussionsupporting
confidence: 88%
“…It has been previously proven that 3D CT is an effective method in the evaluation of SP length, angulation, and other morphological characteristics [3,24]. However, the usual CT tools, such as MPRs, should not be ignored, but used and presented complementarily.…”
Section: Discussionmentioning
confidence: 99%
“…Using only 3D CT tools could lead to misdiagnoses (e.g. false SP: a prominent angle of the SP sheath can be easily confused with a duplicated SP [3]). …”
Section: Discussionmentioning
confidence: 99%
“…In many studies [1,6,13,22], different cut-off values have been determined for Eagle's syndrome. Eagle [6] found that the cut-off value was 25 mm, Basekim et al [1] accepted that it was 40 mm, Jung et al [13] determined a limit value of 45 mm and Ramadan et al [22] recommended that any measurements above 30 mm be described as elongated SP.…”
Section: Referencesmentioning
confidence: 99%
“…Eagle [6] found that the cut-off value was 25 mm, Basekim et al [1] accepted that it was 40 mm, Jung et al [13] determined a limit value of 45 mm and Ramadan et al [22] recommended that any measurements above 30 mm be described as elongated SP. In a study by Ekici et al [9] the mean SP length was found to be longer in males than in females (33.2 ± ± 13.2 vs. 29.6 ± 10.5 mm, p < 0.001).…”
Section: Referencesmentioning
confidence: 99%